Pengaruh Umur Beton Terhadap Kuat Tekan Beton Normal dan HVFA-SCC - RENDI GUSTA WIBOWO (LPPM Universitas Merdeka Madiun, 2022)
In this era, infrastructure development in Indonesia continues. This continues to be pursued to facilitate community activities in various fields. Some of the infrastructure that continues to be built include toll roads and buildings. One of the most important materials for building infrastructure is concrete. Concrete also has various types, including normal concrete and HVFA-SCC. In this study, the two types of concrete will be compared and tested for compressive strength against the age of the concrete. The test were be done at 7 days, 14 days, 21 days, 28 days, and 90 days. The research step starts from preparing materials, conducting material testing, making job mix formulas, making test objects, testing compressive strength, and getting results. The obtained results shown that the fresh concrete of HVFA-SCC has met the self-compacting concrete according to the Slump flow test, L-Box test, and the V-Funnel test. Based on the compressive strength test, the results show that the age of the concrete has an influence on the compressive strength.